Enterprise Architecture Management Education in Academia: An International Comparative Analysis - Martin Robl; Dominik Bork (Complex Systems Informatics and Modeling Quarterly)
Enterprise architecture (EA), although matured in more than 30 years of ongoing research, receives more importance with the increasing dependency of business in IT and the growing complexity of IT systems. The integrated management of a companies’ goals, structures, and processes with respect to the business and IT elements, as well as the representation of impacts triggered by planned changes is educated in different ways at many universities all over the world. There are several techniques, methods, tools, and approaches to transfer the knowledge from the educators to the students, giving them the qualification to support their future employers in handling the EA challenges modern companies are facing. This work gives a detailed comparative analysis of more than twenty international educational offers regarding Enterprise Architecture Management, carves out the commonalities and finds two prototypical courses as a best-practice combining the strongest matches for Business Informatics and Computer Science studies alike.